(3TQM GdLGeY GdcHjQ ddTjHGfis - (3CMeO Hf Ydj GdnqQGRj, CHh HcQ GdLUGU,J (B370 (3g` s; (3CHh YHO Gddg eMeO Hf GdMSf Hf aQbO, GdTjHGfj,J (B189 (3g` s
(3ChdgG (B:s
(3HGH GdfcGM s
(3BNQgG (B:s
(3HGH ef GNJdGa GdTgGOGJ s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdMfajs